Incidence of Drought in Relation to Rainfed Rice Production: an Analysis - Ghosh, Arunava; Majumder, Anurup (International Journal of Bio-resource and Stress Management, 2014)
The distribution of rainfall during a season is more important than its amount. It is therefore, the progressive balance between the receipt and expenditure of the moisture during the growing season, which creates favourable or unfavourable conditions for successful crop production. Several research workers have attempted to study the various aspects of drought on this basis. Their studies have not taken into account the crop yields in determining the agricultural drought. In this paper, the data on rainfall (1945 to 1993) and yield of a crop like rainfed rice in Midnapore district of West Bengal (India) have been analyzed for determining drought threshold value and characterizing agricultural drought. An amount of 20 mm rainfall for two consecutive weeks was identified as drought threshold value in the test location. During drought period, high negative correlation between grain yield and maximum rainfall was observed. The recurrence of drought in relation to rainfed rice has also been studied.